Improving accuracy through density correction in guided wave tomography - Huthwaite,P (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2016)
The accurate quantification of wall loss caused by corrosion is critical to the reliable life estimation of pipes and pressure vessels. Traditional thickness gauging by scanning a probe is slow and requires access to all points on the surface; this is impractical in many cases as corrosion often occurs where access is restricted, such as beneath supports where water collects. Guided wave tomography presents a solution to this; by transmitting guided waves through the region of interest and exploiting their dispersive nature, it is possible to build up a map of thickness. While the best results have been seen when using the fundamental modes A0 and S0 at low frequency, the complex scattering of the waves causes errors within the reconstruction. It is demonstrated that these lead to an underestimate in wall loss for A0 but an overestimate for S0. Further analysis showed that this error was related to density variation, which was proportional to thickness. It was demonstrated how this could be corrected for in the reconstructions, in many cases resulting in the near-elimination of the error across a range of defects, and greatly improving the accuracy of life estimates from guided wave tomography.